2019
DOI: 10.3389/fpsyg.2019.01824
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role of Romantic Attachment in the Relationship Between Attachment to Parents and Aggression

Abstract: Background A secure attachment style could promote more intimacy in romantic relationships, while an insecure attachment style could be correlated with less positive romantic relationships in adulthood. Numerous studies have noted that a secure attachment to parents was correlated with lower levels of aggression, whereas insecure attachments were associated with higher levels of aggression. We aimed to investigate the role of the attachment system as a mediator of the expression of aggressiveness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 77 publications
(114 reference statements)
1
21
0
5
Order By: Relevance
“…Although the relationship with parents continues to assume a crucial support role [126][127][128]-as our findings have also shown-attachment to peers become their essential secure base and source of emotional support [129][130][131]. Consequently, in line with our findings, during this developmental stage, insecure attachment to peers represents the strongest predictor for psychopathological problems, compared to insecure attachment to parents [132,133]. In times of the COVID-19 outbreak and its related restrictions, insecurely attached late adolescents tend to be more vulnerable than their secure peers to the psychopathological consequence of the pandemic [49], both because they are less able to manage their negative feelings (as our study has suggested) and because they would tend to seek less online interactions and emotional support from friends compared to their secure peers [134].…”
Section: Indirect Effects Of Attachment To Parents and Peers Via Alexithymiasupporting
confidence: 83%
“…Although the relationship with parents continues to assume a crucial support role [126][127][128]-as our findings have also shown-attachment to peers become their essential secure base and source of emotional support [129][130][131]. Consequently, in line with our findings, during this developmental stage, insecure attachment to peers represents the strongest predictor for psychopathological problems, compared to insecure attachment to parents [132,133]. In times of the COVID-19 outbreak and its related restrictions, insecurely attached late adolescents tend to be more vulnerable than their secure peers to the psychopathological consequence of the pandemic [49], both because they are less able to manage their negative feelings (as our study has suggested) and because they would tend to seek less online interactions and emotional support from friends compared to their secure peers [134].…”
Section: Indirect Effects Of Attachment To Parents and Peers Via Alexithymiasupporting
confidence: 83%
“…The dysfunctional attitude of the nurturing parent, mainly characterized by a lack of maternal care, comes from a type of traumatic experience such as, for example, neglect or emotional and physical abuse (Carli et al, 2019 ; Cassidy, 1994 ; Santona, De Cesare, Tognasso, De Franceschi, & Sciandra, 2019 ). Despite these reported difficulties associated with the family environment (mostly related to a dysfunctional maternal attachment bond), almost no caregiver attributed the onset of the sibling’s illness to these problems, considering some external cause instead.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, primary caregivers have been shown to present high levels of objective and subjective burden, feelings of guilt, stigma, shyness (Barak & Solomon, 2005;Sin et al, 2016), as well as lack of communication in the path of hyper-care of the sick sibling (Taylor et al, 2001), and widespread difficulties at a psychosocial level . These findings not only highlight the need for carerspecific interventions (Sin et al, 2015;Sin et al, 2016), but also stress the intense involvement of caregivers in the therapeutic and rehabilitative needs of their psychopathological siblings (Dixon, Lyles, & Scott, 1999;Marsh, Appleby, Dickens, Owens, & Young, 1993;Sin et al, 2015).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…In other words, it is not only an outcome but can be also an antecedent. Furthermore, Santona et al [24] showed that high levels of emotional responsiveness can also predict aggressive behaviors during adulthood. Marriage and/or cohabitation, and more in general all stable romantic unions, are linked to better physical and mental health for both children, young people, and adults.…”
Section: Gender Differences In the Impact Of Depression On Love Relationshipsmentioning
confidence: 99%